The most efficient level of winter protein feeding for yearling steers wintered and summer grazed on bluestem pasture. - Smith, E.F.; Baker, F.H.; Cox, R.F.; Holland, L.A. (Kansas Agricultural Experiment Station, 2012)
Yearling steers have been successfully wintered at this station on dry bluestem pasture for the past five winters by feeding 1 1/2 to 2 pounds of cottonseed or soybean oilmeal per head daily. The objective of this test is to determine if the level of winter protein feeding may be reduced without affecting the yearly performance of the steers. Twenty head of good quality Hereford yearling steers, 10 head to a lot, were used in this study. They originated in southeastern Colorado and were purchased as calves in the fall of 1951 for 42 cents a pound. They were used in summer grazing tests on bluestem pasture in 1952. From November 1 until December 31, 1952, when this test started, they were on bluestem pasture supplemented with 1 pound of soybean pellets. During the winter phase of this test, the steers were moved from pasture to pasture every 15 days to minimize any differences due to pastures. The winter pastures in which the steers were grazed were of such size as to vary the stocking rate from 6 to 19 acres per head. All pastures used in the winter had sufficient grass remaining on them for winter use, although they were stocked at a normal rate for the summer of 1952. In addition to dry winter bluestem pasture, the following amounts of protein were fed: Lot 1-1 pound of soybean pellets per head daily. Lot 2-2 pounds of soybean pellets per head daily. The steers were grazed together during the summer of 1953 after the different winter treatments.
Keywords: Beef; Protein; Yearlings; Bluestem pasture; Performance